Preliminary investigation on the feasibility of a clean CAES system coupled with wind and solar energy in China. (15th May 2017) - Chen, Jie; Liu, Wei; Jiang, Deyi; Zhang, Junwei; Ren, Song; Li, Lin; Li, Xiaokang; Shi, Xilin
Abstract: Compressed air energy storage (CAES) is a method of energy storage which can convert the surplus power to the internal energy of compressed air, and regenerates electricity whenever power is needed. A clean CAES system coupled with wind and solar energy was developed to solve the dependence of traditional CAES system on fossil fuels in China. The operating variables of the hybrid system include heat exchanger effectiveness, ambient temperature, mass flow rate, total pressure ratio and compressor/turbine stages. The effect of these variables on the system performance was evaluated, including output power, overall efficiency, energy ratio ( ER ) and heat ratio ( HR ). The parameters, delineating criteria of the potential development localities for the hybrid CAES system sites, such as solar and wind energy resources, abandoned cavities of mines resources used as compressed air containers and the distribution of cross-transmission lines in China were investigated. By this research, it was found that more than 13 major zones were of the capability to support the hybrid system in China. Finally, the environmental and economic benefits of this CAES system were calculated, comparing to the conventional thermal power plants; restrictions and policy supports of the CAES systems in China were discussed as well. Highlights: A clean CAES system was proposed in order to reduce the dependence of fossil fuels. The application of this new system can enhance wind and solar power use in China. The operating variables of this hybrid system and their impacts were evaluated. The criteria of site selection and the suitable sites of this system were presented. The environmental benefits and policy supports of this system were discussed.